Biodegradable polyester composition as well as preparation method and application thereof

By adding erucic acid amide and silicone to polylactic acid materials to compound them with biodegradable copolyester, and using talc powder with specific particle sizes, the problem of insufficient crystallization and processing performance of polylactic acid materials in the injection molding field is solved. , polyester compositions that achieve high mechanical properties and short injection molding cycles are suitable for injection molding products.

CN119264620AActive Publication Date: 2025-01-07KINGFA SCI & TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411543123.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-07
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

The application of polylactic acid materials in the injection molding field is limited by problems such as poor crystallization ability, slow crystallization speed and difficulty in demolding, which leads to unfavorable processing process and affects its wide application in the injection molding field.

Method used

By selecting suitable mass components, especially adding erucic amide and silicone to compound with biodegradable copolyester, and combining with talc powder with appropriate D95 particle size within a specific range, the crystallization of the polyester composition is enhanced by selecting suitable mass components, especially the addition of erucic amide and silicone with biodegradable copolyester and combining with talc powder with a suitable D95 particle size within a specific range, the crystallization of the polyester composition is enhanced. and processability, shorten the injection molding cycle and improve mechanical properties.

Benefits of technology

The excellent mechanical properties and short injection molding cycle of the polyester composition are achieved. The tensile strength, elongation of break and impact strength of the cantilever beam are significantly improved, and the injection molding cycle is shortened, which is suitable for injection molding products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113215100000061
    Figure BDA0005113215100000061
  • Figure BDA0005113215100000071
    Figure BDA0005113215100000071
  • Figure BDA0005113215100000072
    Figure BDA0005113215100000072
Patent Text Reader

Abstract

The invention discloses a biodegradable polyester composition as well as a preparation method and application thereof, and belongs to the technical field of biodegradable materials. The biodegradable polyester composition disclosed by the invention is prepared from the following components in parts by mass: 48 to 77 parts of polylactic acid, 1 to 16 parts of biodegradable copolyester, 18 to 42 parts of talcum powder, 0.05 to 2.6 parts of erucyl amide and 0.005 to 0.08 part of silicone. The D95 particle size of the talcum powder is less than or equal to 17 microns. The biodegradable polyester composition provided by the invention has excellent mechanical properties and processability; the biodegradable polyester composition provided by the invention is short in injection molding period, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biodegradable materials, and in particular relates to a biodegradable polyester composition and a preparation method and application thereof. Background Art

[0002] The selection of biodegradable and bio-based materials is an important way to solve environmental pollution problems and an important support point for sustainable development strategies. It can not only fundamentally solve the white pollution problem, but also greatly reduce the consumption of oil in the material industry and ease the pressure on petrochemical resources. Among them, polylactic acid material has the two advantages of being biodegradable and bio-based and is one of the most important new materials at present.

[0003] Polylactic acid materials have broad application prospects in product packaging, 3D printing, injection molding and other industries due to their reliable biosafety, biodegradability, environmental friendliness, good mechanical properties and easy processing and forming. However, polylactic acid materials have poor crystallization ability, slow crystallization speed and difficulty in demolding, which have caused extremely unfavorable situations in the actual processing process during production, and to some extent limited its application in the field of injection molding. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a biodegradable polyester composition having excellent mechanical properties, good crystallinity and a shorter molding cycle, as well as a preparation method and application thereof.

[0005] To achieve the above object, in a first aspect of the present invention, the present invention provides a biodegradable polyester composition, the biodegradable polyester composition comprising the following components in parts by weight: 48-77 parts of polylactic acid, 1-16 parts of biodegradable copolyester, 18-42 parts of talc, 0.05-2.6 parts of erucamide, and 0.005-0.08 parts of silicone;

[0006] The D of the talc 95 Particle size ≤17μm.

[0007] The biodegradable polyester composition provided by the present invention is prepared by selecting appropriate components by weight, especially selecting erucic acid amide and silicone to be compounded with the biodegradable copolyester, and in addition, combining appropriate D 95 The talcum powder with a particle size within a specific range and the components cooperate with each other, which can effectively improve the crystallinity of the biodegradable polyester composition, thereby shortening the injection molding cycle of the biodegradable polyester composition, improving the processing performance of the composition, and the obtained product also has excellent mechanical properties.

[0008] The D of the talc 95The particle size is obtained by testing with a laser particle size analyzer; specifically, the sample is prepared by a wet method, the talcum powder to be tested and ethanol are mixed to form a particle suspension, which is then added to the measuring cell of the laser particle size analyzer for testing. The instrument used in the test is specifically the LS-POP (6) of Zhuhai OMEC Instrument Co., Ltd.

[0009] As a preferred embodiment of the biodegradable polyester composition of the present invention, the D 95 The particle size is 10-14μm.

[0010] Exemplarily, the D of the talc is 95 The particle size may be any point value or any two point range value between 10-14 μm, for example, 10.52-13.21 μm, or 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, etc.

[0011] Exemplarily, the mass percentage of the polylactic acid can be any point value or any two point range values ​​between 48-77 parts, for example, it can be 50-75 parts, or it can be 48 parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 76 parts, 77 parts, etc.; the biodegradable copolyester can be any point value or any two point range values ​​between 1-16 parts, for example, it can be 3-15 parts, or it can be 1 part, 3 parts, 4 parts, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, etc.; the talc can be any point value or any two point range values ​​between 18-42 parts, for example, it can be 20-40 parts, or it can be 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, etc.; the mass portion of the erucamide can be any point value or any two point range values ​​between 0.05-2.6 parts, such as 0.1-2.5 parts, or 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.5 parts, 0.8 parts, 1.0 parts, 1.4 parts, 1.8 parts, 2.0 parts, 2.4 parts, 2.5 parts, etc.; the mass portion of the silicone can be any point value or any two point range values ​​between 0.005-0.08 parts, such as 0.01-0.07 parts, or 0.005 parts, 0.01 parts, 0.02 parts, 0.03 parts, 0.04 parts, 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, etc.

[0012] Preferably, in the biodegradable polyester composition, the mass percentage of polylactic acid is ≥43%, and the mass percentage of talc is ≥14%.

[0013] Preferably, the mass ratio of erucamide to silicone is (9-36):1.

[0014] Exemplarily, the mass ratio of erucamide to silicone can be any point value or any two point range value between (9-36):1, such as 9:1, 10:1, 15:1, 20:1, 25:1, 30:1, 36:1, etc.

[0015] More preferably, the mass ratio of erucamide to silicone is (18-22):1.

[0016] The silicone used in the present invention includes at least one of polysiloxane and silicone powder.

[0017] The present invention has no particular restriction on the selection of polysiloxane or silicone powder. The polysiloxane may be dimethyl silicone oil, and the silicone powder may be BZSP001 or SY-306.

[0018] As a preferred embodiment of the biodegradable polyester composition of the present invention, the biodegradable polyester composition comprises the following components in parts by weight: 60-65 parts of polylactic acid, 8-10 parts of biodegradable polyester, 23-28 parts of talc, 0.4-1.2 parts of erucamide, and 0.02-0.03 parts of silicone.

[0019] The present invention has found that in the biodegradable polyester composition, the proportions of biodegradable polyester and erucamide will affect the comprehensive performance of the product, and the proportions of other components will also have a certain impact on the performance of the product. When the mass proportions of the components are further selected to be within the above range, the comprehensive effect of the obtained product is better.

[0020] As a preferred embodiment of the biodegradable polyester composition of the present invention, the biodegradable copolyester has a melt flow rate of 1-35 g / 10 min at 190° C. and 2.16 kg.

[0021] The melt flow rate of the biodegradable copolyester at 190°C and 2.16 kg is tested in accordance with ISO-1133-1:2011. It should be noted that the melt flow rate of the biodegradable copolyester may fluctuate by about ±12% during the test. For example, the measured value of the biodegradable copolyester is 30 g / 10 min, and the test results thereof fluctuate between 26-33 g / 10 min in different batches of tests.

[0022] The melt flow rate of the biodegradable copolyester at 190° C. and 2.16 kg can be any point value or any two point range values ​​between 1-35 g / 10 min, for example, 2-30 g / 10 min, 2-20 g / 10 min, 20-25 g / 10 min, 20-30 g / 10 min, etc., or can be 1 g / 10 min, 2 g / 10 min, 4 g / 10 min, 6 g / 10 min, 8 g / 10 min, 10 g / 10 min, 12 g / 10 min, 14 g / 10 min, 16 g / 10 min, 18 g / 10 min, 20 g / 10 min, 22 g / 10 min, 24 g / 10 min, 26 g / 10 min, 28 g / 10 min, 30 g / 10 min, 32 g / 10 min, 35 g / 10 min, etc.

[0023] As a preferred embodiment of the biodegradable polyester composition of the present invention, the mass ratio of the talc powder to the biodegradable copolyester is (3-4):1.

[0024] Exemplarily, the mass ratio of the talc to the biodegradable copolyester may be any point value or any range value between (3-4):1, such as 3.0:1, 3.2:1, 3.4:1, 3.6:1, 3.8:1, 4.0:1, etc.

[0025] The present invention has found that the mass ratio of talcum powder and biodegradable copolyester affects the injection molding cycle and mechanical properties of the product. When the mass ratio of the two is further selected to be (3-4):1, the resulting product has better crystallinity, that is, the injection molding cycle is shorter, and the mechanical properties of the product are also better.

[0026] As a preferred embodiment of the biodegradable polyester composition of the present invention, the molar content of the dextrorotatory D monomer of the polylactic acid is ≤8%.

[0027] The molar content of right-handed D monomer of the polylactic acid is obtained by gas chromatography test; specifically, in the gas chromatography test, the instrument used is Agilent 8860 gas chromatograph, the chromatographic column is CP7502, the FID detector temperature is 200°C, the hydrogen flow rate is 45mL / min, the air flow rate is 450mL / min, and the split ratio is 5:1.

[0028] Exemplarily, the molar content of right-handed D monomer of the polylactic acid can be any point value or any two point range value between ≤8%, for example, it can be 0.5-8.0%, 0.5-3.7%, 0.5-1.4%, etc., or it can be 0.5%, 1%, 1.4%, 1.5%, 2%, 2.5%, 3%, 3.5%, 3.7%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, etc.

[0029] The present invention has found that when the molar content of the right-handed D monomer of the polylactic acid is further selected to be within the above range, it can better cooperate with other components, so that the obtained product has better crystallization performance and a shorter injection molding cycle.

[0030] As a preferred embodiment of the biodegradable polyester composition of the present invention, the biodegradable copolyester includes at least one of polybutylene adipate terephthalate, polybutylene sebacate terephthalate, polybutylene azelaate terephthalate, polybutylene succinate terephthalate and polybutylene succinate.

[0031] Preferably, in the biodegradable copolyester, the molar ratio of aliphatic carboxylic acid to aromatic carboxylic acid is (1-2): 1. Within the above range, the biodegradable property can be met.

[0032] In the second aspect of the present invention, the present invention also provides a method for preparing the biodegradable polyester composition, which comprises the following steps: weighing the dried raw materials, mixing, extruding and granulating to obtain the biodegradable polyester composition.

[0033] As a preferred embodiment of the preparation method of the present invention, the extrusion temperature is 150-240°C.

[0034] In the third aspect of the present invention, the present invention also provides the use of the biodegradable polyester composition in the preparation of injection molding products.

[0035] Exemplarily, the injection-molded product includes any one of a disposable table knife, a disposable fork, and a disposable spoon.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The biodegradable polyester composition provided by the present invention is compounded by selecting appropriate mass parts of components, especially adding a specific type of lubricant and a biodegradable copolyester within a specific melt flow rate range, and further limiting the D of talc. 95The particle size is within a specific range, and the obtained product has excellent mechanical properties and a shorter injection molding cycle; specifically, the obtained product has a tensile strength of more than 46.2MPa, an elongation at break of more than 4.5%, and an Izod notched impact strength of 4.0KJ / m 2 Above, the injection cycle is less than 19s. DETAILED DESCRIPTION

[0038] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0039] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0040] Polybutylene succinate 1 (PBS1): A200 SF NC801, 190°C, measured melt flow rate at 2.16 kg is 30.0 g / 10 min, Zhuhai Jinfa Biomaterials Co., Ltd.

[0041] Polybutylene succinate 2 (PBS2): PBS FZ71PM, 190°C, measured melt flow rate at 2.16 kg is 20.0 g / 10 min, Mitsubishi Chemical Corporation;

[0042] Polybutylene adipate terephthalate 1 (PBAT1): A400 SF NC801, 190°C, measured melt flow rate at 2.16 kg is 20.0 g / 10 min, Zhuhai Jinfa Biomaterials Co., Ltd.

[0043] Polybutylene adipate terephthalate 1 (PBAT2): A400 LF NC801, 190°C, measured melt flow rate at 2.16 kg is 2.0 g / 10 min, Zhuhai Jinfa Biomaterials Co., Ltd.

[0044] Polylactic acid 1: PLA L105, the molar content of right-handed D monomer was 0.5% as measured by gas chromatography, TotalEnergies Corbion;

[0045] Polylactic acid 2: PLA 3251D, the molar content of right-handed D monomer was 1.4% as measured by gas chromatography, Natureworks;

[0046] Polylactic acid 3: FY204, the molar content of right-handed D monomer was 3.7% as measured by gas chromatography, Fengyuan Biotechnology;

[0047] Polylactic acid 4: LX930, the molar content of right-handed D monomer was 8.0% as measured by gas chromatography, Total Energies Corbion;

[0048] Biodegradable copolyester 1: a mixture of PBS1 and PBAT1 in a mass ratio of 1:1, with a measured melt flow rate of 25 g / 10 min at 190 °C and 2.16 kg;

[0049] Biodegradable copolyester 2: PBS2, the measured melt flow rate at 190°C and 2.16 kg is 20 g / 10 min;

[0050] Biodegradable copolyester 3: PBAT1, the measured melt flow rate at 190°C and 2.16 kg is 20 g / 10 min;

[0051] Biodegradable copolyester 4: PBAT2, the measured melt flow rate at 190°C and 2.16 kg is 2 g / 10 min;

[0052] Talc 1: SD-9649, D 95 Particle size 5 is 10.52 μm, from Liaoning Xinda Talc Group;

[0053] Talc 2: T-2, D 95 Particle size 5 is 13.21 μm, Suzhou Youkuang Plastic New Materials Co., Ltd.;

[0054] Talc 3: SL92-10-A, D 95 The particle size is 16.81 μm, Guangxi Longsheng Huamei Talc Development Co., Ltd.

[0055] Talc 4: SD-9462, D 95 Particle size 5 is 8.75 μm, from Liaoning Xinda Talc Group;

[0056] Talc 5: T6, D 95 Particle size is 19.85 μm, Suzhou Youkuang Plastic New Materials Co., Ltd.;

[0057] Erucic acid amide: commercially available;

[0058] Silicone powder 1: BZSP001, Chongqing Baozhuan New Materials Technology Co., Ltd.;

[0059] Silicone powder 2: SY-306, Dongguan Shanyi Plastic Chemical Co., Ltd.

[0060] Examples 1-13 and Comparative Examples 1-7

[0061] The embodiments and comparative examples of the present invention provide a biodegradable polyester composition, and the component contents (parts by weight) of the biodegradable polyester composition are shown in Table 1-2; wherein the parts by weight of silicone 1 in Table 1-2 refer to the parts by weight of the corresponding silicone in the added silicone powder 1, and the parts by weight of silicone 2 refer to the parts by weight of the corresponding silicone in the added silicone powder 2;

[0062] Table 1

[0063]

[0064]

[0065] Table 2

[0066]

[0067] The preparation method of the biodegradable polyester composition provided in Example 1 is:

[0068] The dried raw materials are weighed and added into a twin-screw extruder for mixing, extrusion and granulation to obtain a biodegradable polyester composition;

[0069] During the extrusion process, the temperature of the solid conveying zone is 130-160°C, the temperature of the melting zone is 160-210°C, and the temperature of the melt conveying zone is 210-220°C.

[0070] The preparation methods of the biodegradable polyester compositions provided in Examples 2-13 and Comparative Examples 1-7 are consistent with that in Example 1, and if there are no relevant components, then no component is added. In Table 1-2, “ / ” indicates that the component is not added.

[0071] Effect example

[0072] The effect examples of the present invention verify the performance of the products prepared in the embodiments and comparative examples; the test items include the following aspects:

[0073] 1. Tensile strength: Tested in accordance with GB / T 1040.1-2022. The specimen type is A1 specimen in GB / T37426-2019. The test speed is 50 mm / min.

[0074] 2. Elongation at break:

[0075] The test is carried out in accordance with the requirements of GB / T 1040.2-2022. The specimen type refers to the A1 specimen in GB / T 37426-2019. The test speed is 50 mm / min.

[0076] 3. Izod notch impact strength: According to GB / T 1843-2008, injection molded specimen, specimen size: length | = (80 ± 2) mm, width b = (10.0 ± 0.2) mm, thickness h = (4.0 ± 0.2) mm, notch residual width b N =(8.0±0.2)mm. The notch type is type A. The sample is conditioned for 88h in a test environment with a temperature of (23±2)℃ and a humidity of (50±10)% according to GB / T 2918-2018, and a pendulum with an energy storage of 2.75J is selected for testing; 4. Injection molding cycle: the total time required to complete one injection molding when the same terminal is mass-produced.

[0077] The test results are shown in Table 3;

[0078] Table 3

[0079]

[0080]

[0081] It can be seen from Table 4 that when the technical solution of the present invention is adopted, the obtained product has excellent mechanical properties and crystallization properties; specifically, the obtained biodegradable polyester composition has a tensile strength of more than 46.2 MPa, an elongation at break of more than 4.5%, and an Izod notched impact strength of more than 4.0 KJ / m 2 Above, the injection cycle is less than 19s;

[0082] It can be seen from Example 1, Examples 10-12 and Comparative Example 1 that the selection of talcum powder will affect the performance of the product. 95 When the particle size is not within the range given in the present invention, the obtained product not only has a significantly increased injection cycle, but also has a significantly decreasing mechanical property.

[0083] It can be seen from Example 1 and Comparative Examples 2-4 that erucic acid amide and silicone are indispensable, and whether they are not added or replaced by other similar ingredients, the injection molding cycle of the obtained product is significantly increased;

[0084] It can be seen from Example 1 and Comparative Example 5 that the mass fraction of biodegradable polyester will also affect the performance of the product. When the mass fraction of biodegradable polyester in Comparative Example 5 is too much, the comprehensive performance of the obtained product is significantly reduced; it can be seen from Example 1 and Comparative Example 6 that the mass fraction of erucamide will also affect the performance of the product. When the mass fraction of erucamide in Comparative Example 6 is not within the range, the injection molding cycle of the obtained product is significantly increased; it can be seen from Example 1 and Comparative Example 7 that the mass fraction of silicone will also affect the performance of the product. When the mass fraction of silicone is not within the scope of the present invention, the Izod notched impact strength of the obtained product is significantly reduced and the injection molding cycle is significantly increased.

[0085] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A biodegradable polyester composition, characterized in that The biodegradable polyester composition comprises the following components in parts by weight: 48-77 parts of polylactic acid, 1-16 parts of biodegradable copolyester, 18-42 parts of talc, 0.05-2.6 parts of erucamide, and 0.005-0.08 parts of silicone; The D of the talc 95 Particle size ≤17μm.

2. The biodegradable polyester composition according to claim 1, characterized in that The biodegradable polyester composition comprises the following components in parts by weight: 60-65 parts of polylactic acid, 8-10 parts of biodegradable polyester, 23-28 parts of talc, 0.4-1.2 parts of erucamide, and 0.02-0.03 parts of silicone.

3. The biodegradable polyester composition according to claim 1, characterized in that The biodegradable copolyester has a melt flow rate of 1-35 g / 10 min at 190° C. and 2.16 kg.

4. The biodegradable polyester composition according to claim 1, characterized in that The D of the talc 95 The particle size is 10-14μm.

5. The biodegradable polyester composition according to claim 1, characterized in that: The mass ratio of the talc powder to the biodegradable copolyester is (3-4):

1.

6. The biodegradable polyester composition according to claim 1, characterized in that: The molar content of the dextrorotatory D monomer in the polylactic acid is ≤8%.

7. The biodegradable polyester composition according to claim 1, characterized in that: The biodegradable copolyester includes at least one of polybutylene adipate terephthalate, polybutylene sebacate terephthalate, polybutylene azelaate terephthalate, polybutylene succinate terephthalate and polybutylene succinate.

8. The method for preparing the biodegradable polyester composition according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: weighing the dried raw materials, mixing, extruding and granulating to obtain a biodegradable polyester composition.

9. Use of the biodegradable polyester composition according to any one of claims 1 to 8 in the preparation of injection molding products.

Citation Information

Patent Citations

  • Biodegradable polyester composition as well as preparation method and application thereof

    CN116285247A

  • Biodegradable polyester-based resin composition and film

    JP2001329149A